Oxygen evolution in spin-sensitive pathways - Wu, Tianze (2022)
The overall performance of water electrolysis suffers from the high kinetic barrier in the oxygen evolution reaction (OER) at the anode. Considerable effort has been made on the fundamental understandings of the reaction mechanisms of OER. Recently, the attention has been given to the OER on magnetic catalysts, which is believed being able to promote the kinetics of an OER process from singlet reactants to triplet oxygen. The process in principle involves spin selective electron transfer. Here, we discuss the effects of spin in OER based on the recent advances and summarize our recently proposed mechanisms of the OER in spin-sensitive pathways under the lattice oxygen oxidation mechanism, the interaction of two M−O entity mechanism, and the adsorbate evolution mechanism.